A Luetic Cauda Equina Meningoradiculitis Mimicking a Central Nervous System Lymphoma. Issue 2 (February 2016) - Monticelli, Jacopo; Bazzocchi, Gabriele; Luzzati, Roberto
Abstract : Abstract: We report a case of peculiar neurosyphilis, initially misinterpreted as a lymphoproliferative disorder. This is also the first report to evaluate the utility of positron emission tomography–computed tomography in spinal cord syphilis. Cauda equina radiculitis is a rare manifestation of neurosyphilis whose diagnosis can be supported by the typical syphilitic exanthema. Abstract : Here we describe the case of an extremely rare manifestation of neurosyphilis, a cauda equina meningoradiculitis, and review the diagnosis and manifestations of neurosyphilis.